The Effect of Leader’s Work-Life Balance on Follower’s Creativity: Mediating Effect of Leader-member Exchange Relationship and Moderating Effect of Psychological Ownership - Lee, 지영; Son, Seung Yeon (Korean Journal of Industrial and Organizational Psychology, 2023)
This study paid attention to the positive effects of leaders’ work-life balance, focusing on work-life balance, which has recently emerged as an important issue in organizational human resource management. To this end, this study have three research objectives. First, this study examined the mediating effect of leader-member exchange relationship (LMX) by investigating the effect of leader’s work-life balance on LMX and followers’ creativity. Second, this study investigated whether follower’s psychological ownership had a moderating effect on the influence of LMX on the creativity of the subordinates. Finally, this study attempted to verify the mechanism and boundary conditions of the positive effect of the leader’s work-life balance by examining the mediating effect of the LMX and the moderating effect of the follower’s psychological ownership. As a result of hierarchical multiple regression analysis and process macro analysis based on the dyadic data of 156 leaders and followers working in general companies, LMX fully mediated the relationship between leader’s work-life balance and follower creativity, and follower’s psychological ownership significantly moderated the relationship between LMX and creativity, and finally supported the moderated mediation effect hypothesis. This result means that when leaders perceive themselves as having a work-life balance, this positively affects their relationship with their subordinates and creativity, especially when their psychological ownership is low, LMX is more important to their creativity. This has theoretical implications in that it has expanded the antecedents variables of LMX, focusing on the work-life balance of leaders that has not been previously studied. At the same time, it has practical implications in terms of human resource management by showing the positive effect of the leader’s work-life balance.